2010
DOI: 10.1007/s00404-010-1690-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of P16 and P21 in benign and malignant uterine smooth muscle tumors

Abstract: Our findings suggested that p16 and p21 may be of value as an adjunct to conventional morphologic criteria in the assessment of problematic uterine smooth muscle tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 24 publications
0
23
1
Order By: Relevance
“…Significance was also observed in the expression of p16 among LMS, AUSMT, and leiomyomas (LM) [12] . Thus, the combination of p16 and p53 IHC profiles could represent a useful tool to identify high-risk AUSMT which may potentially recur as LMS [13][14][15][16] . Notably, missense mutations in the TP53 gene represent more than 75% of all p53 mutations in solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Significance was also observed in the expression of p16 among LMS, AUSMT, and leiomyomas (LM) [12] . Thus, the combination of p16 and p53 IHC profiles could represent a useful tool to identify high-risk AUSMT which may potentially recur as LMS [13][14][15][16] . Notably, missense mutations in the TP53 gene represent more than 75% of all p53 mutations in solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that p16 is overexpressed in LMS; therefore, p16 may be useful for distinguishing between benign and malignant USMTs (3,6,7,22). Chen and Yang (7) compared among LMS, STUMP, and other LMs and reported that a strong/moderate-to-significant staining pattern was observed in all LMS and STUMP cases that were positive for p16, whereas weak focal staining was observed in some UL and CL cases.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly downregulated were alcohol dehydrogenase 1A polypeptide, alcohol dehydrogenase 1B polypeptide, insulinlike growth factor 1, c-Jun, c-Fos, and TU3A. Further, p16 and p21 genes [47] were differentially expressed in benign and malignant tumors. There was no difference in p16 and p21 expressions between leiomyomas, atypical leiomyomas, and STUMPs.…”
Section: Mesenchymal Tumorsmentioning
confidence: 94%